Design and synthesis of carbazole carboxamides as promising inhibitors of Bruton's tyrosine kinase (BTK) and Janus kinase 2 (JAK2). Issue 19 (1st October 2015) - Liu, Qingjie; Batt, Douglas G.; Lippy, Jonathan S.; Surti, Neha; Tebben, Andrew J.; Muckelbauer, Jodi K.; Chen, Lin; An, Yongmi; Chang, Chiehying; Pokross, Matt; Yang, Zheng; Wang, Haiqing; et al.
Graphical abstract